Contribution to the Study of Some Hydroxamic Acid Derivatives and Their Use in Gravimetric Determination - Roushdy, M.I.; Issa, Y.M.; EL-Zein, S.M.; EL-Deen Harb, F.M.S. (Asian Journal of Chemistry, 2010)
N-Benzoylphenylhydroxylamine (N-BPHA). Four of its derivative and N-furoyl-N-phenylhydroxylamine have been studied and used successfully for the gravimetric determination of Fe(III), V(V), Ni(II) and Cu(II). The study revealed that the ligands behave as monobasic bidentate ligands. The elements under investigation are successfully determined in the ranges 0.037–0.013 g for Fe, 0.0283– 0.0189 g for V, 0.0284–0.0250 g for Cu and 0.0283–0.0189 g for Ni. The recovery was very high (99.7%) with low standard deviation (0.000208) which reflects the accuracy of this method. The solubility product (Ksp) was small enough (1.25 x 10–9-1 x 10–11 ); so the metal can be determined by weighing the precipitate directly.